2018
DOI: 10.4103/tjo.tjo_70_17
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of unilateral severe simple congenital ptosis

Abstract: Unilateral congenital ptosis with poor levator function of ≤4 mm continues to be a difficult challenge for the oculoplastic surgeon. Surgical correction can be accomplished with unilateral frontalis suspension, maximal levator resection, or bilateral frontalis suspension with or without levator muscle excision of the normal eyelid. Bilateral frontalis suspension was proposed by Beard and Callahan to overcome the challenge of postoperative asymmetry, allowing symmetrical lagophthalmos on downgaze, postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Other surgeons have embraced MLR, to avoid sling-related complications and achieve better outcomes in unilateral and amblyopic cases, in which a compensatory frontalis action might be absent. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other surgeons have embraced MLR, to avoid sling-related complications and achieve better outcomes in unilateral and amblyopic cases, in which a compensatory frontalis action might be absent. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…We found that the downward slide of lashes could be avoided by excising a segment of skin and orbicularis above the crease then suturing both incision lips (more importantly the pretarsal flap) to the resected LPS at the end of the procedure, or to the tarsal plate instead. [ 6 ] Twelve of the MLR treated eyes had this additional step, with no postoperative lash ptosis recorded ( P = 0.092).…”
Section: Discussionmentioning
confidence: 99%
“…Severe congenital ptosis with poor levator function of ≤ 4 mm is not easy for the oculoplastic surgeon to deal with. 5 The type of Surgery for the correction of congenital ptosis is based on surgeon's choice which may be frontalis suspension (FS) or MLR, Different studies are available which support both types. 6 In both choices, the surgery is a challenge because of cosmetic and physiological implications.…”
Section: Introductionmentioning
confidence: 99%